How Followers Differing in Career Motivation Gain Career Profits from Transformational Leaders: A Longitudinal Moderated Mediation Model - Baethge, Anja; Rigotti, Thomas; Vincent-Hoeper, Sylvie (Frontiers in Psychology, 2017)
Although transformational leadership is among the most thoroughly examined leadership theories, knowledge regarding its association with followers’ career outcomes is still limited. Furthermore, the underlying mechanisms explaining how transformational leaders affect their employees’ career success are yet not well understood. Based on theoretical assumptions about the processes involved in setting the goal of “making a career”, we propose an indirect effect of transformational leadership on subjective and objective career success via development opportunities that depends on the level of career motivation of employees. We conducted a longitudinal study with two measurement occasions separated by 13 months with 320 employees of a large IT company. Respondents provided ratings online on their direct supervisor’s transformational leadership, their own development opportunities, and career motivation at T1; subjective career success was rated at both time points, whereas objective indicators of career transitions were rated at T2 retrospectively. Using structural equation modeling, we tested the proposed moderated mediation model. The results indicated that transformational leadership increased subordinates’ subjective career success via development opportunities. In addition, and contrary to theoretical reasoning, the indirect effect was not significant for employees with high career motivation. Thus, employees high in career motivation appeared not to benefit from the development opportunities offered by transformational leaders. The results are discussed in light of tailored leadership that takes the aspirations, and needs of followers into account.